(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2004)
The gold-polymetallic deposit of Shahumyan is located in Syunick Region of the Republic of Armenia. It is displayed by a number of veins of latitude extent with sharp incidence northwards and southwards and stretch from 100 up to 500 m. The investigation of the deposit has been realized on horizons of 600, 700, 780, 820 and 860 m by means of underground mountain drillings and pit-holes. Sampling has been implemented, using both furrow and core procedures at 4 m radius. The analysis of the network density of sampling has been accomplished on basic formulas of statistics. After analyzing the results obtained it was indicated that possible expand of sampling radius is up to 12 m, providing the principle on accurate economic assessment of the deposit.